Awareness of memory deficits in subjective cognitive decline, mild cognitive impairment, Alzheimer's disease and Parkinson's disease. (10th November 2014) - Lehrner, Johann; Kogler, Sandra; Lamm, Claus; Moser, Doris; Klug, Stefanie; Pusswald, Gisela; Dal-Bianco, Peter; Pirker, Walter; Auff, Eduard
ABSTRACT: Background: Impaired awareness of memory deficits has been recognized as a common phenomenon in Alzheimer's disease (AD) and research is now increasingly focusing on awareness in groups at risk for future dementia. This study aimed to determine whether levels of awareness differ among healthy elderly people and patients with subjective cognitive decline (SCD), amnestic and non-amnestic subtypes of mild cognitive impairment (aMCI, naMCI), Alzheimer's disease (AD) and Parkinson's disease (PD), to explore correlates of awareness and to establish frequencies of memory over- and underestimation within each diagnostic group. Methods: 756 consecutive outpatients of a memory clinic and 211 healthy controls underwent thorough neuropsychological testing. Impairment of awareness was measured as the difference between subjective memory appraisals (16-item questionnaire on current memory-related problems in everyday life) and objective memory performance (15-item delayed recall task). Subgroups of over- and underestimators were classified using percentile ranks of controls. Results: At group level, awareness significantly decreased along the naMCI→aMCI→AD continuum, with naMCI patients showing a tendency towards overestimation of memory dysfunction. PD patients showed accurate self-appraisals as long as memory function was largely unaffected. However, there was a considerable between-group overlap in awareness scores. Furthermore, different correlates of awareness were observed depending on the diagnostic group. In general, unawareness seems to be associated with decreased cognitive performance in various domains (especially memory), higher age and lower levels of depression and self-reported functional impairment. Conclusion: Impaired awareness is an important symptom in aMCI. Yet, given the considerable variability in awareness scores, longitudinal studies are required to evaluate their predictive power.